This section is an attempt to extend the concept of an interval-valued intuitionistic fuzzy soft rough set [52] to the case of an interval-valued neutrosophic rough set.
Proof.
(i) Let
a
∈
A
and
x
∈
f
(
a
)
. Then for
y
∈
f
(
a
)
, we have
{
x
,
y
}
⊆
f
(
a
)
and hence
inf
μ
σ
(
y
)
≥
⋀
{
inf
μ
σ
z
:
∃
a
∈
A
{
x
,
z
}
⊆
f
(
a
)
}
. Consequently,
(11)
⋀
y
∈
f
(
a
)
inf
μ
σ
(
y
)
≥
⋀
inf
μ
σ
z
:
∃
a
∈
A
x
,
z
⊆
f
a
.
And so
(12)
⋀
x
∈
f
(
a
)
⋀
y
∈
f
(
a
)
inf
μ
σ
(
y
)
≥
⋀
inf
μ
σ
z
:
∃
a
∈
A
x
,
z
⊆
f
a
.
Similarly, it can be shown that
(13)
⋀
x
∈
f
(
a
)
⋀
y
∈
f
(
a
)
sup
μ
σ
(
y
)
≥
⋀
sup
μ
σ
z
:
∃
a
∈
A
x
,
z
⊆
f
a
.
Thus, we get
(14)
⋀
inf
μ
σ
z
:
∃
a
∈
A
x
,
z
⊆
f
a
,
⋀
sup
μ
σ
z
:
∃
a
∈
A
x
,
z
⊆
f
a
⊆
⋀
x
∈
f
a
⋀
y
∈
f
a
inf
μ
σ
y
,
⋀
x
∈
f
a
⋀
y
∈
f
a
sup
μ
σ
y
.
In a similar manner it can be shown that
(15)
⋁
inf
ν
σ
z
:
∃
N
_
S
σ
,
⋁
sup
ν
σ
z
:
∃
a
∈
A
x
,
z
⊆
f
a
⊆
⋁
x
∈
f
a
⋁
y
∈
f
a
inf
ν
σ
y
,
⋁
x
∈
f
a
⋁
y
∈
f
a
sup
ν
σ
y
.
In a similar manner it can be shown that
(16)
⋁
x
∈
f
(
a
)
⋁
y
∈
f
(
a
)
inf
ω
σ
(
y
)
,
⋁
x
∈
f
(
a
)
⋁
y
∈
f
(
a
)
sup
ω
σ
(
y
)
×
⋁
{
inf
ω
σ
z
:
∃
a
∈
A
(
x
,
z
⊆
f
a
)
}
,
⋁
{
sup
ω
σ
z
:
∃
a
∈
A
(
x
,
z
⊆
f
a
)
}
⊆
⋁
x
∈
f
a
⋁
y
∈
f
a
inf
ω
σ
y
,
⋁
x
∈
f
a
⋁
y
∈
f
a
sup
ω
σ
y
.
From (14), (15), and (16) we observe that
(17)
N
_
S
(
σ
)
⊆
⋀
x
∈
f
a
⋀
y
∈
f
a
inf
μ
σ
y
,
⋀
x
∈
f
a
⋀
y
∈
f
a
sup
μ
σ
y
,
h
h
h
i
h
h
⋁
x
∈
f
a
⋁
y
∈
f
a
inf
ν
σ
y
,
⋁
x
∈
f
a
⋁
y
∈
f
a
sup
ν
σ
y
,
h
h
h
h
h
⋁
x
∈
f
a
⋁
y
∈
f
a
inf
ω
σ
y
,
⋁
x
∈
f
a
⋁
y
∈
f
a
sup
ω
σ
y
.
Now we prove that
(18)
⋀
x
∈
f
a
⋀
y
∈
f
a
inf
μ
σ
y
,
⋀
x
∈
f
a
⋀
y
∈
f
a
sup
μ
σ
y
,
h
i
⋁
x
∈
f
a
⋁
y
∈
f
a
inf
ν
σ
y
,
⋁
x
∈
f
a
⋁
y
∈
f
a
sup
ν
σ
y
,
h
⋁
x
∈
f
a
⋁
y
∈
f
a
inf
ω
σ
y
,
⋁
x
∈
f
a
⋁
y
∈
f
a
sup
ω
σ
y
⊆
N
_
S
σ
.
Let us suppose that
a
∈
A
such that
{
x
,
z
}
⊆
f
(
a
)
. Then
a
∈
f
(
a
)
,
z
∈
f
(
a
)
, and hence
(19)
inf
μ
σ
(
z
)
≥
⋀
x
∈
f
(
a
)
⋀
y
∈
f
(
a
)
inf
μ
σ
y
.
Consequently,
(20)
⋀
inf
μ
σ
z
:
∃
a
∈
A
x
,
z
⊆
f
a
≥
⋀
x
∈
f
(
a
)
⋀
y
∈
f
(
a
)
inf
μ
σ
y
.
Similarly, it can be shown that
(21)
⋀
sup
μ
σ
z
:
∃
a
∈
A
x
,
z
⊆
f
a
≥
⋀
x
∈
f
a
⋀
y
∈
f
a
sup
μ
σ
y
.
Thus we get
(22)
⋀
x
∈
f
(
a
)
⋀
y
∈
f
(
a
)
inf
μ
σ
(
y
)
,
⋀
x
∈
f
(
a
)
⋀
y
∈
f
(
a
)
sup
μ
σ
(
y
)
⊆
⋀
inf
μ
σ
z
:
∃
a
∈
A
x
,
z
⊆
f
a
,
⋀
sup
μ
σ
z
:
∃
a
∈
A
x
,
z
⊆
f
a
.
In a similar manner it can be shown that
(23)
⋁
x
∈
f
(
a
)
⋁
y
∈
f
(
a
)
inf
ν
σ
(
y
)
,
⋁
x
∈
f
(
a
)
⋁
y
∈
f
(
a
)
sup
ν
σ
(
y
)
⊆
⋁
inf
ν
σ
z
:
∃
a
∈
A
x
,
z
⊆
f
a
,
⋁
sup
ν
σ
z
:
∃
a
∈
A
x
,
z
⊆
f
a
.
In a similar manner it can be shown that
(24)
⋁
x
∈
f
(
a
)
⋁
y
∈
f
(
a
)
inf
ω
σ
(
y
)
,
⋁
x
∈
f
(
a
)
⋁
y
∈
f
(
a
)
sup
ω
σ
(
y
)
⊆
⋁
inf
ω
σ
z
:
∃
a
∈
A
x
,
z
⊆
f
a
,
⋁
sup
ω
σ
z
:
∃
a
∈
A
x
,
z
⊆
f
a
.
From (22), (23), and (24) we observe that
(25)
⋀
x
∈
f
a
⋀
y
∈
f
a
inf
μ
σ
y
,
⋀
x
∈
f
a
⋀
y
∈
f
a
sup
μ
σ
y
,
⋁
x
∈
f
a
⋁
y
∈
f
a
inf
ν
σ
y
,
⋁
x
∈
f
a
⋁
y
∈
f
a
sup
ν
σ
y
,
⋁
x
∈
f
a
⋁
y
∈
f
a
inf
ω
σ
y
,
⋁
x
∈
f
a
⋁
y
∈
f
a
sup
ω
σ
y
⊆
N
_
S
(
σ
)
.
From (17) and (25), we have
(26)
N
_
S
σ
=
x
,
⋀
x
∈
f
a
⋀
y
∈
f
a
inf
μ
σ
y
,
⋀
x
∈
f
a
⋀
y
∈
f
a
sup
μ
σ
y
,
h
h
h
h
h
h
⋁
x
∈
f
a
⋁
y
∈
f
a
inf
ν
σ
y
,
⋁
x
∈
f
a
⋁
y
∈
f
a
sup
ν
σ
y
,
h
h
h
h
h
h
⋁
x
∈
f
a
⋁
y
∈
f
a
inf
ω
σ
y
,
h
h
h
h
h
h
h
⋁
x
∈
f
a
⋁
y
∈
f
a
sup
ω
σ
y
:
x
∈
U
.
(ii) Proof is similar to that in (i).
Proof.
(1)–(4) are straightforward.
(5) We have
(27)
σ
=
x
,
inf
μ
σ
x
,
sup
μ
σ
x
,
h
h
inf
ν
σ
x
,
sup
ν
σ
x
,
h
h
inf
ω
σ
x
,
sup
ω
σ
x
:
x
∈
U
,
λ
=
x
,
inf
μ
λ
x
,
sup
μ
λ
x
,
h
h
[
inf
ν
λ
(
x
)
,
sup
ν
λ
(
x
)
]
,
h
h
inf
ω
λ
x
,
sup
ω
λ
x
:
x
∈
U
,
σ
∩
λ
=
x
,
inf
μ
σ
∩
λ
x
,
sup
μ
σ
∩
λ
x
,
h
h
[
inf
ν
σ
∩
λ
x
,
sup
ν
σ
∩
λ
x
]
,
h
h
inf
ω
σ
∩
λ
x
,
sup
ω
σ
∩
λ
x
:
x
∈
U
.
Now
(28)
N
_
s
σ
∩
λ
=
x
,
⋀
inf
μ
σ
∩
λ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
,
h
h
h
h
h
h
h
h
⋀
sup
μ
σ
∩
λ
y
:
∃
a
∈
A
x
,
y
⊆
f
a
,
h
h
h
h
h
h
⋁
inf
ν
σ
∩
λ
z
:
∃
a
∈
A
x
,
y
⊆
f
a
,
h
h
h
h
h
h
h
⋁
sup
ν
σ
∩
λ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
,
h
h
h
h
h
h
⋁
inf
ω
σ
∩
λ
y
:
∃
a
∈
A
x
,
y
⊆
f
a
,
h
h
h
h
h
h
h
⋁
sup
ω
σ
∩
λ
y
:
∃
a
∈
A
x
,
y
⊆
f
a
:
h
h
h
h
x
∈
U
x
,
⋁
inf
μ
σ
y
:
∃
a
∈
A
x
,
y
⊆
f
a
=
x
,
⋀
min
inf
μ
σ
y
,
inf
μ
λ
y
:
h
h
h
h
h
h
h
h
i
h
h
h
∃
a
∈
A
x
,
z
⊆
f
a
,
h
h
h
h
h
h
h
h
⋀
min
sup
μ
σ
y
,
sup
μ
λ
y
:
⋀
min
inf
μ
σ
y
,
inf
μ
λ
y
:
h
h
h
h
h
h
h
h
h
h
h
∃
a
∈
A
x
,
z
⊆
f
a
,
h
h
h
h
h
h
⋁
max
inf
ν
σ
y
,
inf
ν
λ
y
:
h
h
h
h
h
i
h
h
h
h
h
∃
a
∈
A
x
,
z
⊆
f
a
,
h
h
h
h
h
h
h
⋁
max
sup
ν
σ
y
,
sup
ν
λ
y
:
h
h
h
h
h
h
h
i
h
h
h
⋁
max
inf
ν
σ
y
,
inf
ν
λ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
,
h
h
h
h
h
h
⋁
max
inf
ω
σ
y
,
inf
ω
λ
y
:
h
h
h
h
h
h
h
h
h
h
∃
a
∈
A
x
,
z
⊆
f
a
,
h
h
h
h
h
h
h
⋁
max
sup
ω
σ
y
,
sup
ω
λ
y
:
h
h
h
h
h
h
h
h
h
h
⋁
max
inf
ω
σ
y
,
inf
ω
λ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
:
x
∈
U
.
Since
(29)
min
inf
μ
σ
y
,
inf
μ
λ
y
≤
inf
μ
σ
y
,
min
inf
μ
σ
y
,
inf
μ
λ
y
≤
inf
μ
λ
y
we have
(30)
⋀
min
inf
μ
σ
y
,
inf
μ
λ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
≤
⋀
inf
μ
σ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
,
⋀
min
inf
μ
σ
y
,
inf
μ
λ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
≤
⋀
inf
μ
λ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
.
Consequently,
(31)
⋀
min
inf
μ
σ
y
,
inf
μ
λ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
≤
min
⋀
inf
μ
σ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
,
h
h
h
h
h
h
h
⋀
inf
μ
λ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
.
Similarly we can get
(32)
⋀
min
sup
μ
σ
y
,
sup
μ
λ
y
:
∃
a
∈
A
x
,
y
⊆
f
a
≤
min
⋀
sup
μ
σ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
,
h
h
h
h
i
h
h
h
h
⋀
sup
μ
λ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
.
Again since
(33)
max
inf
ν
σ
y
,
inf
ν
λ
y
≥
inf
ν
σ
y
,
max
inf
ν
σ
y
,
inf
ν
λ
y
≥
inf
ν
λ
y
,
we have
(34)
⋁
max
inf
ν
σ
y
,
inf
ν
λ
y
:
∃
a
∈
A
x
,
y
⊆
f
a
≥
⋁
inf
ν
σ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
,
⋁
max
sup
ν
σ
y
,
sup
ν
λ
y
:
∃
a
∈
A
x
,
y
⊆
f
(
a
)
≥
⋁
sup
ν
σ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
.
Consequently,
(35)
⋁
max
inf
ν
σ
y
,
inf
ν
λ
y
:
∃
a
∈
A
{
x
,
y
}
⊆
f
a
≥
max
⋀
inf
ν
σ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
,
h
h
h
h
h
h
h
h
h
⋀
inf
ν
λ
y
:
∃
a
∈
A
x
,
y
⊆
f
a
.
Similarly we can get
(36)
⋁
max
sup
ν
σ
y
,
sup
ν
λ
y
:
∃
a
∈
A
x
,
y
⊆
f
(
a
)
≥
max
⋀
sup
ν
σ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
,
h
h
h
h
h
h
h
h
⋀
sup
ν
λ
y
:
∃
a
∈
A
x
,
y
⊆
f
a
.
Again since
(37)
max
inf
ω
σ
y
,
inf
ω
λ
y
≥
inf
ω
σ
y
,
max
inf
ω
σ
y
,
inf
ω
λ
y
≥
inf
ω
λ
y
,
we have
(38)
⋁
max
inf
ω
σ
y
,
inf
ω
λ
y
:
∃
a
∈
A
x
,
y
⊆
f
a
≥
⋁
inf
ω
σ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
,
⋁
max
(
sup
ω
σ
y
,
sup
ω
λ
(
y
)
)
:
∃
a
∈
A
{
x
,
y
}
⊆
f
(
a
)
≥
⋁
sup
ω
σ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
.
Consequently,
(39)
⋁
max
inf
ω
σ
y
,
inf
ω
λ
y
:
∃
a
∈
A
x
,
y
⊆
f
a
≥
max
⋀
inf
ω
σ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
,
h
h
h
h
h
h
h
h
h
⋀
inf
ω
λ
y
:
∃
a
∈
A
x
,
y
⊆
f
a
.
Similarly we can get
(40)
⋁
max
(
sup
ω
σ
y
,
sup
ω
λ
(
y
)
)
:
∃
a
∈
A
{
x
,
y
}
⊆
f
(
a
)
≥
max
⋀
sup
ω
σ
y
:
∃
a
∈
A
x
,
y
⊆
f
a
,
h
h
h
h
h
h
h
h
⋀
sup
ω
λ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
.
Using, (31)–(40) we get from (28)
(41)
N
_
s
σ
∩
λ
⊆
N
_
s
σ
∩
N
_
s
λ
.
(6) Proof is similar to (5).
(7) We have
(42)
σ
=
x
,
inf
μ
σ
x
,
sup
μ
σ
x
,
h
h
h
h
inf
ν
σ
x
,
sup
ν
σ
x
,
h
h
i
h
inf
ω
σ
x
,
sup
ω
σ
x
:
x
∈
U
,
λ
=
x
,
inf
μ
λ
x
,
sup
μ
λ
x
,
h
h
h
h
inf
ν
λ
x
,
sup
ν
λ
x
,
h
h
i
h
inf
ω
λ
x
,
sup
ω
λ
x
:
x
∈
U
,
σ
∪
λ
=
x
,
inf
μ
σ
∪
λ
x
,
sup
μ
σ
∪
λ
x
,
h
h
h
h
inf
ν
σ
∪
λ
x
,
sup
ν
σ
∪
λ
x
,
h
h
i
h
inf
ω
σ
∪
λ
x
,
sup
ω
σ
∪
λ
x
:
x
∈
U
.
Now
(43)
N
¯
s
σ
∪
λ
=
x
,
⋀
inf
μ
σ
∪
λ
y
:
∃
a
∈
A
x
,
y
⊆
f
a
,
h
h
h
h
h
h
⋀
sup
μ
σ
∪
λ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
,
h
h
i
h
⋁
inf
ν
σ
∪
λ
z
:
∃
a
∈
A
x
,
y
⊆
f
a
,
h
h
h
h
h
⋁
sup
ν
σ
∪
λ
y
:
∃
a
∈
A
x
,
y
⊆
f
a
,
h
h
i
h
⋁
inf
ω
σ
∪
λ
y
:
∃
a
∈
A
x
,
y
⊆
f
a
,
h
h
h
h
h
⋁
sup
ω
σ
∪
λ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
:
h
h
h
x
,
⋀
inf
μ
σ
∪
λ
y
:
∃
a
∈
A
x
,
y
⊆
f
a
,
x
∈
U
=
x
,
⋀
max
inf
μ
σ
y
,
inf
μ
λ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
hhhhhhhhhh
∃
a
∈
A
x
,
z
⊆
f
a
,
hhhhhh
⋀
max
sup
μ
σ
y
,
sup
μ
λ
y
:
⋀
max
inf
μ
σ
y
,
inf
μ
λ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
h
h
h
h
h
h
h
h
h
h
∃
a
∈
A
x
,
z
⊆
f
a
,
hhhhh
⋁
min
inf
ν
σ
y
,
inf
ν
λ
y
:
hhhhhhhhhh
∃
a
∈
A
x
,
z
⊆
f
a
hhhhhhhhhh
∃
a
∈
A
x
,
z
⊆
f
a
,
hhhhhh
⋁
min
sup
ν
σ
y
,
sup
ν
λ
y
:
⋁
min
inf
ν
σ
y
,
inf
ν
λ
y
:
hhhhhhhhhh
∃
a
∈
A
x
,
z
⊆
f
a
hhhhhhhhhh
∃
a
∈
A
x
,
z
⊆
f
a
,
hhhhh
⋁
min
inf
ω
σ
y
,
inf
ω
λ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
hhhhhhhhhh
∃
a
∈
A
x
,
z
⊆
f
a
,
hhhhhh
⋁
min
sup
ω
σ
y
,
sup
ω
λ
y
:
⋁
min
inf
ω
σ
y
,
inf
ω
λ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
h
h
h
h
h
h
h
h
h
h
∃
a
∈
A
x
,
z
⊆
f
a
:
x
∈
U
.
Since
(44)
max
inf
μ
σ
y
,
inf
μ
λ
y
≥
inf
μ
σ
y
,
max
inf
μ
σ
y
,
inf
μ
λ
y
≥
inf
μ
λ
y
we have
(45)
⋀
max
inf
μ
σ
y
,
inf
μ
λ
y
:
∃
a
∈
A
x
,
y
⊆
f
a
≥
⋀
inf
μ
σ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
,
⋀
max
inf
μ
σ
y
,
inf
μ
λ
y
:
∃
a
∈
A
x
,
y
⊆
f
a
≥
⋀
inf
μ
λ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
.
Consequently,
(46)
⋀
max
inf
μ
σ
y
,
inf
μ
λ
y
:
∃
a
∈
A
x
,
y
⊆
f
(
a
)
≥
max
⋀
inf
μ
σ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
,
h
h
h
h
h
h
h
h
⋀
inf
μ
λ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
.
Similarly we can get
(47)
⋀
max
sup
μ
σ
y
,
sup
μ
λ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
≥
max
⋀
sup
μ
σ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
,
h
h
h
h
i
h
h
h
⋀
sup
μ
λ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
.
Again since
(48)
min
inf
ν
σ
y
,
inf
ν
λ
y
≤
inf
ν
σ
y
,
min
inf
ν
σ
y
,
inf
ν
λ
y
≤
inf
ν
λ
y
we have
(49)
⋁
min
inf
ν
σ
y
,
inf
ν
λ
y
:
∃
a
∈
A
x
,
y
⊆
f
a
≤
⋁
inf
ν
σ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
,
⋁
min
min
ν
σ
y
,
min
ν
λ
y
:
∃
a
∈
A
x
,
y
⊆
f
a
≤
⋁
inf
ν
λ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
.
Consequently,
(50)
⋁
min
inf
ν
σ
y
,
inf
ν
λ
y
:
∃
a
∈
A
x
,
y
⊆
f
a
≤
min
⋁
inf
ν
σ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
,
H
H
H
H
H
H
⋁
inf
ν
λ
y
:
∃
a
∈
A
x
,
y
⊆
f
a
.
Similarly we can get
(51)
⋁
min
sup
ν
σ
y
,
sup
ν
λ
y
:
∃
a
∈
A
x
,
y
⊆
f
a
≤
min
⋁
sup
ν
σ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
,
h
j
h
h
h
h
h
h
⋁
sup
ν
λ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
.
Again since
(52)
max
inf
ω
σ
y
,
inf
ω
λ
y
≤
inf
ω
σ
y
,
max
inf
ω
σ
y
,
inf
ω
λ
y
≤
inf
ω
λ
y
,
we have
(53)
⋁
min
inf
ω
σ
y
,
inf
ω
λ
y
:
∃
a
∈
A
x
,
y
⊆
f
a
≤
⋁
inf
ω
σ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
,
⋁
min
inf
ω
σ
y
,
inf
ω
λ
y
:
∃
a
∈
A
x
,
y
⊆
f
a
≤
⋁
inf
ω
λ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
.
Consequently,
(54)
⋁
min
inf
ω
σ
y
,
inf
ω
λ
y
:
∃
a
∈
A
x
,
y
⊆
f
a
≤
min
⋁
inf
ω
σ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
,
h
h
h
h
h
h
h
h
⋁
inf
ω
λ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
.
Similarly we can get
(55)
⋁
min
sup
ω
σ
y
,
sup
ω
λ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
≤
min
⋁
sup
ω
σ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
,
h
h
h
h
h
h
h
h
⋁
sup
ω
λ
y
:
∃
a
∈
A
x
,
z
⊆
f
a
.
Using (46)–(55), we get from (43)
(56)
N
_
s
σ
∪
N
_
s
λ
⊆
N
_
s
σ
∩
λ
.
(8) Proof is similar to (7).